Implikasi Hukum Kesenjangan Regulasi dalam Pencatatan Identitas Ayah - Abdul Rahim, Abdul Rahim; Syamsuddin, Darussalam; Amin, Abd. Rauf Muhammad; Musyahid , Achmad; Bhatti, Muhammad Safdar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study examines the regulation of the minimum marriage age in the Compilation of Islamic Law as a form of progressive ijtihad based on maqaṣid al-shari‘ah. This research emphasizes how the marriage age requirement reflects the integration of maslahah fardiyyah (individual welfare) and maslahah ‘a’iliyyah (family welfare), both of which are legal principles aimed at protecting children and strengthening family institutions. Adopting normative legal methods with a statutory, conceptual, and philosophical approach, this research combines classical and contemporary Islamic legal thought and relevant laws and regulations in Indonesia. The theory of maṣlaḥah, developed by scholars such as al-Ghazali, al-Juwayni, al-Shaṭibi, and Ramadan al-Būṭi, forms the main theoretical foundation, particularly through the lens of ḍawabiṭ al-maṣlaḥah (parameters of public interest). These theories emphasize the preservation of life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), and lineage (ḥifẓ al-nasl) as central objectives of Islamic law. The findings show that the marriage age provision in the Compilation of Islamic Law is not merely an administrative policy but a legal strategy aligned with maqaṣid-based reasoning to prevent child marriage and its associated harms. This approach reflects a contextual reading of Islamic law that is responsive to socio-cultural changes, while remaining faithful to its foundational values. The study concludes that reinforcing a maṣlaḥah-based framework is essential to harmonize Islamic legal principles with national law and to ensure the well-being of individuals and families in contemporary society.